The Innovation of Beetroot-based Processed Products to Improve Women's Economy in Padusan Village, Pacet District, Mojokerto Regency - Irawati, Santi; Rahmadani, Desi; Chandra, Tjang Daniel; Soseco, Thomas; Nurjanah, Nunung (Angstrom Centre of Education, 2024)
Padusan Village, located in the Mojokerto district, has been identified as having significant potential for beetroot processing. In response to this opportunity, a community service team embarked on a project to empower local women by providing them with the necessary skills and knowledge to produce a variety of beetroot-based processed products. These products included beetroot tepung, crackers, cheese sticks, and wedang wuluh drinks. Throughout the initiative, the women were closely supported by students specializing in catering, who guided them through each step of the production process, from familiarizing them with the ingredients to mastering the art of dough preparation. They demonstrated remarkable progress in their understanding of food processing techniques and showed enthusiasm in exploring the diverse culinary possibilities offered by beetroot. Looking ahead, future community service endeavors aim to further empower these women by facilitating the transition to large-scale production and providing assistance in developing effective marketing strategies. By leveraging their newfound skills and tapping into potential market demand, the women of Padusan Village can enhance their economic prospects and contribute to the growth and prosperity of their community.